Penerapan Corporate Social Responsibility (Csr) Terhadap Profitabilitas Perusahaan (Studi Kasus Pada Pt Bank Danamon Indonesia,Tbk) - Linda Arisanty Razak; Muh Aris Pasigai; Husnul Khatimah (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
This study aims to analyze differences before and after the implementation of a CSR program on profitability carried out by PT. Bank Danamon Indonesia, Tbk. The type of research used in this research is quantitative descriptive research. Data obtained by documentation techniques in the form of financial statements of PT. Bank Danamon Indonesia Tbk before the implementation of CSR in 2002-2009 and after the implementation of CSR in 2010-2017. The calculation technique used in this study is to calculate the percentage of profitability ratios (ROA) of PT. Bank Danamon Indonesia Tbk. While the data analysis techniques used in this study used descriptive statistical tests and tested hypotheses with the Paired Sample T Test analysis method using a tool in the form of SPSS 23.  The results showed that there were no differences before and after the implementation of CSR. There is no difference in profitability measured by ROA allegedly because social activities and environmental activities as a form of corporate responsibility for the surrounding environment and social are not good enough so that the impact on the company has not been seen. Besides, the types of banking companies that do not have a direct impact on natural resources also can be one of the factors there is no difference in profitability at PT. Bank Danamon Indonesia Tbk.